Optimal Time and Opportunity Cost of Job Search in Low-income Groups: an Out-of-the-job Search Model - Tamara Todorova; Veselina Dzharova (Modern Economy, 2010)
Our paper studies the causes of poverty from the perspective of job search. We show that poor people remain poor because they have less time and initial endowment to search for a better job. Initial endowment is key to successful job search, as one can afford not to work and search longer for a better job. Having an initial en-dowment, a worker is able to educate or re-qualify himself. Working long hours and obtaining low pay, poor people have little time to look for a better job. Low-paid, low-skilled jobs rarely allow on-the-job search like high-paid positions where with the help of contacts and a lot of idle time professionals seek better jobs. Quit-ting in order to find a better job increases the opportunity cost of search for poorer people. Since they do not have any accumulated income, they can only live off their salary. With less income and time, poorer people are less likely to get educated since education requires both wealth and free time. But being less educated, they are likely to remain poor as education is a promise for success in contemporary society. Thus, they re-main in the vicious circle of poverty. In order to prove this hypothesis we investigate optimal search time for a better job as dependent on factors such as wage rate, individual's income, education, and skills.
Keywords: J22; J64; 330; Job search; Optimal search time; Employment; Poverty; Initial endowment